Evaluation of morphological variations of mandibular bone in adult bruxers using CBCT: A cross-sectional study - Estelle Casazza; Benoit Ballester; Clémence Vernet; Camille Philip-Alliez; Anne Raskin (PLoS ONE, 2026)
This cross-sectional study aimed to establish whether a difference exists between the mandibular bone density and the mandibular angle values of adult bruxer and non-bruxer patients, based on a CBCT analysis. CBCT scans of bruxer and non-bruxer patients were analysed with two software packages, 3D Slicer® and Romexis®. Bone density in the alveolar bone below and immediately adjacent to the apices of teeth 31, 33, 34, 41, 43, 44, and the mesial apices of teeth 36 and 46, was recorded in Hounsfield units with 3D Slicer®. The mandibular angle between the corpus and ramus tangent lines was measured using Romexis® software. 113 CBCT scans were included in the study of alveolar bone density, of which 78 were used to study mandibular angle values. A statistically significant difference (p < 0.05) was noted between the density values of the two groups, with higher values in bruxers than in non-bruxers. Mandibular angle values were significantly lower in bruxers (p < 0.05). This cross-sectional study based on CBCT imaging showed certain morphological differences between the mandibles of bruxers and those of non-bruxers. Further studies are needed to supplement this preliminary research, in particular prospective studies.